2013
DOI: 10.1007/s13762-012-0143-6
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals pollution in the soils of suburban areas in big cities: a case study

Abstract: Soil pollution in agricultural areas surrounding big cities is a major environmental problem. Tabriz is the largest city in the northwest of Iran and the fourth largest city in the country. Soil samples were taken from 46 sites in the suburbs of the Tabriz city, and separate samples were taken from control site and analyzed. The results indicated that the mean pH value of the soil samples was 9.29, while the mean EC value was 354.33 ls/cm and the amount of TOC and TOM was 0.99 and 1.7 %, respectively. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Anthropogenic sources of Cd in soils are related to application of manure, or phosphate fertilizers can lead increasing cadmium in the soil [1-4, 14, 15]. The mean Zn concentration in this study compared with some citiesis similar; in this study is: 98.8, in the Iran (Tabriz and Isfahan) is 98.27 and 111.5 respectively, in the China is 94.9 (mg\kg) [1,3,15]. The Zn concentration was lower than CCEM [16].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Anthropogenic sources of Cd in soils are related to application of manure, or phosphate fertilizers can lead increasing cadmium in the soil [1-4, 14, 15]. The mean Zn concentration in this study compared with some citiesis similar; in this study is: 98.8, in the Iran (Tabriz and Isfahan) is 98.27 and 111.5 respectively, in the China is 94.9 (mg\kg) [1,3,15]. The Zn concentration was lower than CCEM [16].…”
Section: Discussionsupporting
confidence: 54%
“…Industrial and agricultural development has been largely responsible for pollution of the environment with heavy metals (HMs).The mobilization of metals from industrial regions by transport with seepage waters or by windblown dust may also be an important source of soil contamination [1][2][3].Cement industry is one of the sources for environmental pollution. Cement dust contains HMs pollutants hazardous to the biotic environment with impact for vegetation, human health, animal health and ecosystem [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, sodium tripolyphosphate is an ingredient of many detergents whose use has been associated with eutrophication (Köhler 2006). Furthermore, accumulation of heavy metals and micropollutants in the environment may cause toxicity through the food chain, distort the ecological balance (Schwarzenbach et al 2006;Ternes and Joss 2006;Escher and Fenner 2011;Taghipour et al 2013) and negatively affect humans and animals after long exposure time or after bioaccumulation and biomagnification (Snyder et al 2003;Arjoon et al 2013;González-Naranjo and Boltes 2013). Also pathogenic microorganisms in grey water may cause diseases that result in either morbidity or mortality depending on the severity and duration of the exposure (Eriksson et al 2002;Ottoson and Stenström 2003;Birks and Hills 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Alfisols, Vertisols, Aridisols and Inceptisols are major soil orders, which occur predominantly in rainfed regions of India. Soil pollution in agricultural areas surrounding big cities is a major environmental problem (Taghipour et al 2013). The urban and dense cities of India with significant industrial waste generation have been found to have heavy metal contaminated soils.…”
Section: Introductionmentioning
confidence: 99%